Evaluación de la gestión administrativa de la empresa “Aguas del Chuno - EP” del cantón Chone durante el periodo 2014 – 2018 - Macías Zambrano, Karina Cecibel (2021)
The research was carried out with the objective of evaluating the administrative management of the company Aguas del Chuno EP of the canton Chone from the 2014-2018 period to determine the efficiency and management of resources, establish the scientific and legal sciences generating a theoretical support in the study and its importance; as well as the use of scientific methods such as inductive, deductive and analytical that allowed the efficient development of activities where the organizational structure of the entity's administrative management system was identified through an interview with the manager, who stated that an evaluation is being carried out periodic review of strengths, weaknesses, opportunities and threats; As well as a design of strategies for the new management model, we choose a better development of the processes that are executed; Subsequently, the efficiency and effectiveness of administrative management was determined, where 28.6% stated that they carry out activities directed by the motivation of their superiors and 61.9% applied control within the work area. Finally, with the results obtained, the following weaknesses will be obtained: Lack of timely decision-making, health emergencies that cause an alteration of the established and operational program, deficiency in the definition of institutional objectives, low motivation of employees and lack of control in each of the entity's areas. Thus, we will proceed to determine an improvement proposal that contributes to the development of organizational development and implement strategies to comply with decision-making.